Budget Performance Analysis Using the Value for Money Method in The Office of The Ministry of Religion, Bantaeng District - Risna Nur Istiqamah; Sahade Sahade; Mukhammad Idrus (ProBisnis : Jurnal Manajemen, 2023)
This research aims to determine how the budget performance of the Office of the Ministry of Religion of Bantaeng Regency is based on the Value for Money method. The variable in this research is Performance Measurement with Value for Money Method. Value for money. The population in this study were all programs/activities at the Office of the Ministry of Religion of Bantaeng Regency. The sample used purposive sampling method. Data collection techniques used are interviews and documentation. The data analysis technique used descriptive quantitative analysis method (Descriptive Quantitative Analysis Method). Based on the results of the study that: (1) In 2018 the Ministry of Religion of Bantaeng Regency was managing its finances economically, while in 2019 the Ministry of Religion of Bantaeng Regency was not economical. (2) In 2018 the performance of the Ministry of Religion of Bantaeng Regency was efficient but not optimal, while in 2019 the performance of the Ministry of Religion of Bantaeng Regency was also not efficient. (3) In 2018 and 2019 the performance of the Ministry of Religion of Bantaeng Regency has not been effective.